PSS DESIGN INNOVATION: PROTOTYPING IN PRACTICE. (May 2020) - Ruvald, R.; Larsson, A.; Johansson Askling, C.; Bertoni, A.
Abstract: Heavy equipment manufacturers recognise an opportunity to realise customer value gains through offering new Product-Service Systems. Such transition implies a radical shift in how new systems are designed. Based on a set of interviews the paper investigates how radical PSS innovation can be enabled by the use of physical prototypes as boundary object to navigate early PSS design ambiguity. On such basis, suggestions for augmenting existing support tools are made in relation to the existing literature.